2009
DOI: 10.1007/s10517-009-0621-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dermorphin Analogue Sedatin on Indomethacin-Induced Injury to the Gastric Mucosa

Abstract: Administration of indomethacin (250 mg/kg) to mice was followed by the formation of severe ulcerative and erosive injury to the gastric mucosa, inhibition of DNA synthesis, and development of oxidative stress. Fivefold pretreatment with sedatin (100 microg/kg) decreased the area of indomethacin-induced ulcers and erosions, stimulated DNA synthesis, and reduced the severity of oxidative stress. Non-arginine dermorphin analogue did not stimulate DNA synthesis and had no effect on the degree of oxidative stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Due to the recent literary data, the most explored representatives of oligopeptides with gastroprotective properties are met-enkephaline (His-D-Trp-Ala-Trp-D-Phe-Lys-NH2) [27,28] and leu-enkephaline (Tyr-Gly-Gly-Phe-Leu) [27][28][29], demorphine (Н-Tyr-D-Ala-Phe-Gly-Tyr-Pro-Ser-NH 2 ) and sedatine (H-ArgTyr-D-Ala-Phe-Gly-OH) [5,30], pentadecapeptide BPC 157 (GlyGlu-Pro-Pro-Pro-Gly-Lys-Pro-Ala-Asp-Asp-Ala-Gly-Leu-Val) [10,[31][32][33]; proline-and hydroxyproline-containing products…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the recent literary data, the most explored representatives of oligopeptides with gastroprotective properties are met-enkephaline (His-D-Trp-Ala-Trp-D-Phe-Lys-NH2) [27,28] and leu-enkephaline (Tyr-Gly-Gly-Phe-Leu) [27][28][29], demorphine (Н-Tyr-D-Ala-Phe-Gly-Tyr-Pro-Ser-NH 2 ) and sedatine (H-ArgTyr-D-Ala-Phe-Gly-OH) [5,30], pentadecapeptide BPC 157 (GlyGlu-Pro-Pro-Pro-Gly-Lys-Pro-Ala-Asp-Asp-Ala-Gly-Leu-Val) [10,[31][32][33]; proline-and hydroxyproline-containing products…”
Section: Discussionmentioning
confidence: 99%
“…Copyright: ©2015 Nasadyuk et al Н-thymidine showed that the administration of sedatin in different doses stimulated DNA synthesis in epithelium of the gastric mucosa [5,30]. Endogenous opioids have been implicated in the process of gastric sensitivity and gastric motor responses, and impairment of antinociceptive opioid pathways, that is hypothesized to contribute to the pathogenesis of functional dyspepsia [46].…”
Section: Gastroprotective Oligopeptides 3/6mentioning
confidence: 99%
See 3 more Smart Citations